Indonesia’s Aggregated Accounting Egulatory Compliance - Agus Setyadi; Rusmin Rusmin; Greg Tower; Alistair M Brown (Jurnal Akuntansi dan Auditing Indonesia, 2009)
The purpose of this study is to examine aggregate Indonesian Accounting Regulatory Compliance (IARCagg) by analyzing 220 Indonesian non-financial companies annual reports for yearly-ending 2006 listed on the Indonesia Stock Exchange (IDX). Agency theory offers insights into the listed companies’ IARC practices, particularly in ascertaining whether enhanced corpo-rate governance and differing ownership and governance structures lead to increased IARC. This study uses a 29-item index derived from Indonesian accounting standards on inven-tory, fixed assets, and depreciation to measure the level of regulatory compliance of Indonesian listed companies. Analysis reveals a level of 60.61% compliance with accounting rules. Regression analy-sis shows that the variables of firm size and return on assets are significant predictors of IAR-Cagg. Bigger and more profitable companies have far higher compliance with accounting rules.There is a data limitation in that this study is a cross sectional examination that focuses on Indonesian accounting standards: inventory, fixed assets, and depreciation. Nevertheless, this cross sectional examination provides the latest version of firms listed on the IDX and accurate in-formation on the business environment in Indonesia as at 31 December 2006.Although Indonesian firms may have complied with more than 50% of the key accounting rule provisions, regulatory intervention is still needed to ensure there is full compliance with In-donesian accounting regulations. Such regulation might include sanctions as promulgated by multilateral financial organizations.No previous accounting compliance studies have been performed using an Indonesian data sample set. Critically, this study considers whether the concepts of ownership structure and corporate governance determine accounting compliance.Keywords: Indonesia, listed firms, compliance, and accounting standards